Peningkatan Produktivitas Budidaya Jamur Tiram melalui Partisipasi Masyarakat dan Penerapan Teknologi Tepat Guna - Uswatun Chasanah; Asri Munzilin; Ach. Agil Dzikrullah; Keisha Farellia Putri Lindra; Safika; Nihro Afandi; A.Afif Amrullah; Mochammad Su’eb; Imam Mawardi (Transformative Service Journal, 2025)
Oyster mushrooms (Pleurotus ostreatus) are a horticultural commodity with high economic value and increasing market demand, both from households and the culinary industry. However, at the local farmer level, productivity remains low due to limitations in cultivation methods, production facilities, and technical knowledge. Therefore, this community engagement program was essential to address the need for increased production capacity and to support the economic independence of mushroom farmers. This program was implemented in Jugruk Rejosari Village, Kandangan Sub-district, Benowo District, Surabaya, in collaboration with the farmer group “Jamur Jaya Sukses” as part of the Bangun Desa Unggul program initiated by Baitulmaal Muamalat. The interventions included the distribution of 2,000 baglogs, the implementation of automated temperature and humidity control systems, the use of fermented agricultural waste as a growing medium, steam sterilization, and a micro misting system. Technical mentoring was also provided through consultation with mushroom cultivation practitioners from Magetan. The results demonstrated increased cultivation efficiency, such as reduced crop failure rates, shorter harvesting periods, and lower operational costs due to the use of local waste-based substrates. Additionally, mushroom productivity significantly improved, from an average of 0.6 kg per baglog to 0.9 kg per baglog. This program is expected to serve as a practical model for the sustainable development of oyster mushroom cultivation in other regions.